Pelatihan Pembuatan Bahan Ajar Membaca pada Guru-Guru Sekecamatan Cimanggu - Raditya Pratama; Rama Cipta Prasetya; Ngabdullah Ali (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2021)
Teachers' literacy teaching creativity is the ability of teachers to constantly develop literacy materials or lesson materials and be able to create an interesting and active atmosphere and be able to modify lessons. Creativity development in literacy learning is also very important and teachers are required to demonstrate and show the creativity process. One alternative that teachers can do is to create, compile and develop effective, efficient and creative literacy teaching materials. This study aims to determine the development of teacher creativity in making reading, writing and counting teaching materials. The method used was descriptive qualitative method. The research subjects were teachers in Cimanggu sub-district. The results of this study indicate that: creative teachers are teachers who are able to develop pedagogical skills, namely being able to compile more varied teaching materials. In addition, they are able to improve pedagogical skills in developing reading, writing and counting literacy teaching materials so that learning becomes more innovative and effective. The development of quality literacy teaching materials can support human resources who are more competent, creative, productive and have high fighting values to face the era of globalization.